2021
DOI: 10.21203/rs.3.rs-831694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercellular Propagation and Aggregate Seeding of Mutant Ataxin-1

Abstract: Intercellular propagation of aggregated protein inclusions along actin-based tunneling nanotubes (TNTs) has been reported as a means of pathogenic spread in Alzheimer’s, Parkinson’s and Huntington’s Disease. Propagation of oligomeric-structured polyglutamine-expanded ataxin-1 (Atxn1[154Q]) has been reported in the cerebellum of a Spinocerebellar ataxia type 1 (SCA1) knock-in mouse to correlate with disease propagation. In this study, we investigated whether a physiologically-relevant polyglutamine-expanded ATX… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Attempts to manipulate tau aggregation clearance by application of bafilomycin A1, an inhibitor of late-stage autophagy via inhibition of autophagosome-lysosome fusion, and application of Bortezomide, a proteasome enzyme complex inhibitor, had little effect. Similarly, our study (Huang et al, 2022) found that induction of autophagy with 500 nM rapamycin or arrest of autophagy by 60 µM chloroquine redistributed diffuse RFP-ATXN1[82Q] into aggregates but did not clear the aggregates. Notably, induction of autophagy clears aggregation-resistant and diffuse RFP-ATXN1[30Q] protein, while arrest of autophagy induced the formation of RFP-ATXN1[30Q] into large aggregates.…”
Section: Proteasomal and Lysosomal Dysfunctionmentioning
confidence: 52%
See 3 more Smart Citations
“…Attempts to manipulate tau aggregation clearance by application of bafilomycin A1, an inhibitor of late-stage autophagy via inhibition of autophagosome-lysosome fusion, and application of Bortezomide, a proteasome enzyme complex inhibitor, had little effect. Similarly, our study (Huang et al, 2022) found that induction of autophagy with 500 nM rapamycin or arrest of autophagy by 60 µM chloroquine redistributed diffuse RFP-ATXN1[82Q] into aggregates but did not clear the aggregates. Notably, induction of autophagy clears aggregation-resistant and diffuse RFP-ATXN1[30Q] protein, while arrest of autophagy induced the formation of RFP-ATXN1[30Q] into large aggregates.…”
Section: Proteasomal and Lysosomal Dysfunctionmentioning
confidence: 52%
“…Taken together, their work as well as the other studies illustrated here suggest a model by which amplification of TNT formation as a protective mechanism allows diseased or vulnerable cells to export their inclusions and in exchange import healthy mitochondria and lysosomes. However, Chastagner et al (2020) and Huang et al (2022) demonstrate seeding of non-aggregation prone proteins by aggregation-prone proteins following transfer. How do we reconcile the two seemingly disparate functions of TNTs?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNTs also spread alpha synuclein and amyloid proteins between cells [76][77][78][79]. Similarly, the polyglutamine-expanded ATXN1 protein (ATXN1[82Q]), DNA-binding protein of 43 kDa (TDP-43), and Tau could transmit intercellularly via TNTs [80][81][82][83][84]. Although cellular models played a key role in discovering pathogenic protein transfer via TNTs, recent advancements in imaging technologies have identified TNT-like transfer of disease protein in vivo [73].…”
Section: Spreadmentioning
confidence: 99%